Histopathologic patterns of female genital tuberculosis with clinical correlation: a 10-year (2013-2022) retrospective cross-sectional study - Kidest Melkamu; Amanuel Damie; Senait Ashenafi; Moti Sori; Selfu Girma; Sofia Yimam; Negash Baye; Belachew Shote (BMC, 2024)
Abstract Objective Underdiagnosis of female genital tuberculosis (FGTB) often leads to infertility. In this study, we aimed to determine the site and histopathologic patterns of FGTB and its correlation with clinical presentation and acid-fast bacilli (AFB) status. Methods A retrospective cross-sectional study was conducted on 122 patients with a histopathological diagnosis of FGTB at the Department of Pathology, College of Health Sciences (CHS), Tikur Anbessa Specialized Hospital (TASH), Addis Ababa University (AAU), from January 1, 2013, to August 30, 2022. Results Female genital tuberculosis was found in 0.94% of the gynecology specimens examined. The most common presentations were menstrual disturbance, abdominopelvic pain, and infertility. Among patients with FGTB, 4.6% exhibited misleading clinical and radiologic findings, leading to suspicion of malignancy and subsequent aggressive surgical management. The endometrium was the most frequently affected organ, followed by the fallopian tube, ovary, cervix, and vulva. In the majority of tuberculous endometritis cases (53.3%), histopathology revealed early-stage granulomas. Acid-fast bacilli were found in a significant proportion (42.6%) of FGTB tissues with TB histopathology. The ovary had the highest rate of AFB detection, followed by the fallopian tube, endometrium, and cervix. Conclusion Female genital tuberculosis should be considered in reproductive-age women presenting with menstrual irregularities, abdominopelvic pain, infertility, or an abdominopelvic mass. The endometrium is commonly affected, displaying early granulomas with low AFB positivity.